2010
DOI: 10.1007/s00412-010-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear reformation after mitosis requires downregulation of the Ran GTPase effector RanBP1 in mammalian cells

Abstract: The GTPase Ran regulates nucleocytoplasmic transport in interphase and spindle organisation in mitosis via effectors of the importin beta superfamily. Ran-binding protein 1 (RanBP1) regulates guanine nucleotide turnover on Ran, as well as its interactions with effectors. Unlike other Ran network members that are steadily expressed, RanBP1 abundance is modulated during the mammalian cell cycle, peaking in mitosis and declining at mitotic exit. Here, we show that RanBP1 downregulation takes place in mid to late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Particularly, RCC1 accumulates on chromatin at anaphase onset in cycling XEE (Arnaoutov and Dasso, 2003), and we wondered whether RRR complex-dependent partitioning of RCC1 between the chromatin-bound and -unbound pools might play a role in this phenomenon. Earlier studies have demonstrated mitotic regulation of mammalian RanBP1 through degradation and phosphorylation (Ciciarello et al, 2010; Hwang et al, 2011). We did not find any evidence that RanBP1 was subject to degradation during multiple cell cycles within cycling XEE (Figure 4A, upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, RCC1 accumulates on chromatin at anaphase onset in cycling XEE (Arnaoutov and Dasso, 2003), and we wondered whether RRR complex-dependent partitioning of RCC1 between the chromatin-bound and -unbound pools might play a role in this phenomenon. Earlier studies have demonstrated mitotic regulation of mammalian RanBP1 through degradation and phosphorylation (Ciciarello et al, 2010; Hwang et al, 2011). We did not find any evidence that RanBP1 was subject to degradation during multiple cell cycles within cycling XEE (Figure 4A, upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. S5) and are hypersensitive to Impβ1 knockdown (see Section 3.1), and that Impβ1 is known to regulate multiple aspects of mitosis [20,27], we investigated whether the decreased viability in Impβ1 siRNA-treated cells may be associated with a block in cell cycle/mitotic progression and whether this relates to the induction of cell death. To this end, we performed propidium iodide staining of malignant MCF10CA1h cells treated twice with 10 nM Impβ1 siRNA followed by flow cytometry (Fig.…”
Section: Impβ1 Sirna Induces Death In Malignant Cellsmentioning
confidence: 99%
“…Indeed, it controls Anillin localization and triggers asymmetric membrane elongation during anaphase, defining spindle positioning at the center of the dividing cell (Silverman-Gavrila et al, 2008 ; Kiyomitsu and Cheeseman, 2012 ). Finally, during cytokinesis the RanGTP pathway regulates the activity of the kinesin Kif14/Nabkin in actin bundling (Carleton et al, 2006 ; Samwer et al, 2013 ) and coordinates nuclear membrane and NPC reassembly (Harel et al, 2003 ; Walther et al, 2003 ; Ciciarello et al, 2010 ; Roscioli et al, 2010 ; Forbes et al, 2015 ; Figure 1D ).…”
Section: Understanding the Rangtp Pathway Through The Identification mentioning
confidence: 99%